Dynamic Changes and Interactions between Microbial Communities and Volatile Flavor Compounds in Fermented Pigskin - Xueling CHEN; Lili JI; Qi WANG; Xinxin NIU; Zhuo CHEN; Cheng LIAO; Kaixian ZHU; Kunyi LIU (Shipin gongye ke-ji)
To investigate the role of microorganisms in the formation of fermented pigskin's quality, samples were collected during the fermentation stage, and high-throughput sequencing and metabolomics techniques were applied to analyze the microorganisms and volatile metabolites during the fermentation process of pigskin. The results showed that the dominant microorganisms gradually changed from Acinetobacter, Fusarium, Aspergillus, and Phomopsis and Candida in the early stage of fermentation to Bacillus, Acinetobacter, Staphylococcus, Mucor, Penicillium and Monascus. On the 10 th day of fermentation, they further changed to Bacillus, Acinetobacter, Myroides, Mucor, Penicillium and Arthrinium, while, Bacillus, Acinetobacter, Enterococcus, Mucor, Penicillium and Monascus became the dominant microorganisms in the later stage of fermentation. Meanwhile, 528 volatile metabolites were detected during the fermentation process, of which 14 volatile metabolites were the key differential metabolites before and after pigskin fermentation (VIP>1, |log2FC|>1, P<0.05, ROAV>200). Pearson correlation analysis of the above dominant microorganisms and key differential metabolites, and it was found that there were significant correlations (P<0.05) between Acinetobacter, Aspergillus, Candida, Fusarium, Myroides, Bacillus, Enterococcus, Staphylococcus, Mucor, Penicillium, Monascus with 9 terpenes, 2 ketones, 2 aldehydes, 1 sulfur-containing compound. In summary, the research results provide a theoretical basis for the quality dynamic control of the pigskin fermentation process.